Analysing Ice Crystalline Structure Using Domination And Fractals - et. al., M.Raji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Water plays an important role within the evolution and survival of life. Ice is a solid substance which is obtained by water in its frozen state. Fractals are capable of describing many irregularly shaped objects. The aim of this Paper is about the Crystalline Structure of Ice which is a connected simple graph and identifies that its Structure is a dominating set and it exhibits the fractal structure of the graph.